Analyzing temporal variations of AGN emission line profiles in the context of (dusty) cloud structure formation in the broad line region - Esser, Johannes (Astronomy and astrophysics, 2019)
The formation processes and the exact appearance of the dust torus and broad line region (BLR) of active galactic nuclei (AGN) are under debate. Theoretical studies show a possible connection between the dust torus and BLR through a common origin in the accretion disk. However observationally the dust torus and BLR are typically studied separately. NGC 4151 is possibly one of the best suited Seyfert 1 galaxies for simultaneous examinations because of its high number of both photometric and spectroscopic observations in the past. Here we compare changes of the dust radius to shape variations of broad emission lines (BEL). While the radius of the dust torus decreased by almost a factor of two from 2004 to 2006 shape variations can be seen in the red wing of BELs of NGC 4151. These simultaneous changes are discussed in a dust and BEL formation scheme. We also use the BEL shape variations to assess possible cloud distributions, especially in azimuthal direction, which could be responsible for the observed variations. Our findings can best be explained in the framework of a dust inflated accretion disk. The changes in the BELs suggest that this dusty cloud formation does not happen continuously, and over the whole accretion disk, but on the contrary in spatially confined areas over rather short amount of times. We derive limits to the azimuthal extension of the observed localized BEL flux enhancement event.
Gesehen am 04.06.2019